1967
DOI: 10.1083/jcb.32.2.467
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Studies of Organotypic Cultures of Rat Dorsal Root Ganglia Following X-Irradiation in Vitro

Abstract: Long-term organotypic cultures of rat dorsal root ganglia were cxposed to a single 40 kR dose of 184 kvp X-rays and studied in the living and fixed states by light or electron microscopy at 1-14 day intervals thereafter. Within the first 4 days following irradiation, over 30% of the neurons display chromatolytic reactions (cccentrlc nuclci, peripheral dispersal of Nissl substance, central granular zone) as well as abnormal nuclcolar changes and dissociation of ribosomes from endoplasmic reticulum cisternae. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…Such dilation of the endoplasmic-reticulum cisternae of irradiated autonomic ganglion cells and satellite cells were observed earlier in the rat (Nicolescu et al, 1966;Forssmann and Rouiller, 1966) and guinea pig (Sulkin et aI., 1968). and Masurovsky et al (1967) reported the same phenomenon in the neurons of irradiated rat dorsal root ganglia.…”
Section: Discussionsupporting
confidence: 54%
“…Such dilation of the endoplasmic-reticulum cisternae of irradiated autonomic ganglion cells and satellite cells were observed earlier in the rat (Nicolescu et al, 1966;Forssmann and Rouiller, 1966) and guinea pig (Sulkin et aI., 1968). and Masurovsky et al (1967) reported the same phenomenon in the neurons of irradiated rat dorsal root ganglia.…”
Section: Discussionsupporting
confidence: 54%
“…I n PNS and CNS, 6 replicate cultures were set up for both myelin formation and maintenance, and 10 cultures were prepared of ANS. Details of these culture methods are published elsehwere: P N S by Bunge et al (1967); CNS by Allerand and Murray (1968); and ANS by Murray and Benitez (1967).…”
Section: Tissuesmentioning
confidence: 99%
“…changes included accumulation of lipofuscin pigment in the ganglion cells, local aggregation of satellite cells nodules of nageotte and neuronal vacuolar degeneration (10). The effects of X-irradiation on ganglion cells of the lower back in rats were investigated by Masurovsky et al (11). In the first days, a sharp degeneration in the satellite cells was noted and later sequestration, vacuolization and autolysis were detected.…”
Section: Discussionmentioning
confidence: 99%
“…In the first days, a sharp degeneration in the satellite cells was noted and later sequestration, vacuolization and autolysis were detected. All these changes were possibly linked to metabolic and membrane permeability (11). Acquired immunodeficiency syndrome-associated changes were evaluated by Burdo et al (12) through examination of the dorsal root ganglia of CD8-depleted simian immunodeficiency virus-infected rhesus macaques.…”
Section: Discussionmentioning
confidence: 99%